Analysis of Brand Awareness and Halal Label on Brand Attitude - Rismawati, Rika; Komariah, Kokom; Mulia Z, Faizal (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study aims to analyze the effect of brand awareness and halal label on brand attitude of Wardah cosmetic customers in Sukabumi City. The method used is descriptive-analytical approach with quantitative research techniques. Data were collected through observation, interviews, questionnaires, literature study, and documentation, involving 94 respondents who are consumers of Wardah products. Data analysis used multiple correlation analysis and multiple linear regression, supported by partial (t-test) and simultaneous (f-test) significance tests with the help of SPSS 26 software. The results showed that there is a strong relationship between brand awareness and halal labeling on brand attitude, with a correlation value of 0.742. The contribution of the two variables in influencing brand attitude is 88.8%, while 11.2% is influenced by other variables not studied. The t-test reveals that both brand awareness and halal labeling partially have a positive and significant influence on brand attitude. In addition, the results of the f-test show that the two variables simultaneously significantly influence brand attitude